Synopsis of Hexasepalum (Rubiaceae), the priority name for Diodella and a new species from Brazil - Cabaña Fader, Andrea Alejandra (2016)
Fil: Cabaña Fader, Andrea Alejandra. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.